Sleep, activity, and diet in harmony: unveiling the relationships of chronotype, sleep quality, physical activity, and dietary intake - Günal, Ahmet Murat (Frontiers in Nutrition, 2023)
Introduction This cross-sectional study aims to explore the intricate relationships among chronotype, sleep quality, physical activity, and dietary intake in a diverse cohort of 3,072 (50.2% female) participants residing in İstanbul, Türkiye. Methods This study utilized established measurement tools, including the Morningness-Eveningness Questionnaire (MEQ) to assess chronotype, the Pittsburgh Sleep Quality Index (PSQI) to evaluate sleep quality, the International Physical Activity Questionnaire Short Form (IPAQ-SF) to measure physical activity, and a 24-h dietary recall method to assess dietary intake. Results The findings of this study revealed compelling associations. Firstly, a robust association was observed between sleep quality and chronotype (OR: 2.265; 95% CI: 1.954–2.626; p < 0.001) as well as physical activity (OR: 0.836; 95% CI: 0.750–0.932; p = 0.002). Specifically, evening chronotypes are more likely to have poor sleep quality, while highly active individuals tend to report lower sleep quality. Transitioning from inactivity to high activity was associated with a 16.4% increase in the odds of transitioning from normal to poor sleep, while a shift from an evening to a morning chronotype was linked to a substantial 126.5-fold increase in the odds of moving from poor to normal sleep. Additionally, morning chronotypes also display distinctive dietary patterns, characterized by higher energy, protein, and fat intake, and reduced carbohydrate intake. Poor sleep quality is associated with increased energy and macronutrient consumption. Discussion These findings underscore the intricate relationships of chrononutrition within the context of sleep quality, physical activity, and dietary choices. The study underscores the significance of personalized interventions to effectively address specific health behaviors, highlighting the complexity of chrononutrition’s role in promoting overall health and wellbeing.